2017
DOI: 10.2967/jnumed.116.188052
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging Evaluation of Four σ1 Radiotracers in Nonhuman Primates

Abstract: The σ receptors (S1Rs) are implicated in a variety of diseases including Alzheimer disease and cancer. Previous PET S1R radiotracers are characterized by slow kinetics or off-target binding that impedes their use in humans. Here, we report the first PET imaging evaluation in rhesus monkeys of 4 F-labeled spirocyclic piperidine-based PET radiotracers (F- to F-). Baseline scans for the 4 radiotracers were obtained on an adult male rhesus monkey. Blocking scans were obtained with the S1R-selective agonist SA4503 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Although affinity and selectivity are essential criterion, in vivo pharmacokinetics is an equally important parameter as recent studies have shown that 18 F-FTC-146 had unfavourably slow pharmacokinetic properties for human use 30 , 31 . Noteworthily, it was shown in non-human primate that despite having lower affinity (S)- 18 F-fluspidine (K i = 2.30 nM) displayed more favourable pharmacokinetics for human use than (R)- 18 F-fluspidine (K i = 0.52 nM) 32 . Hence, taking into account all these considerations, to date (S)- 18 F-fluspidine appears to be the most suitable candidate for S1R PET imaging in human.…”
Section: Introductionmentioning
confidence: 99%
“…Although affinity and selectivity are essential criterion, in vivo pharmacokinetics is an equally important parameter as recent studies have shown that 18 F-FTC-146 had unfavourably slow pharmacokinetic properties for human use 30 , 31 . Noteworthily, it was shown in non-human primate that despite having lower affinity (S)- 18 F-fluspidine (K i = 2.30 nM) displayed more favourable pharmacokinetics for human use than (R)- 18 F-fluspidine (K i = 0.52 nM) 32 . Hence, taking into account all these considerations, to date (S)- 18 F-fluspidine appears to be the most suitable candidate for S1R PET imaging in human.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently developed ( R )-(+)- and ( S )-(−)-[ 18 F]fluspidine [ 31 ], two specific radioligands for Sig1R PET with promising preclinical properties and distinctive kinetics [ 33 , 35 ]. In this publication, we investigated the suitability of both enantiomers of [ 18 F]fluspidine to image Sig1R in different mouse tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify pridopidine's mechanism of action, we used PET imaging to assess the receptor occupancy of pridopidine at previously used clinical doses. (S)-(-)-[ 18 F] Fluspidine (termed here [ 18 F] Fluspidine for simplicity) proved to be a selective and suitable radioligand for neuroimaging of S1R availability in preclinical PET studies and a recent first-in-human PET investigation [19][20][21][22][23]. (S)-(-)-[ 18 F] Fluspidine shows a more favorable metabolic profile compared with its (R)-(-)-enantiomer, and its binding to the S1R is reversible, whereas binding of the (R)-(-)-enantiomer is irreversible [20].…”
Section: Introductionmentioning
confidence: 99%